2017
DOI: 10.1073/pnas.1616199114
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fission by protein crowding

Abstract: Membrane fission, which facilitates compartmentalization of biological processes into discrete, membrane-bound volumes, is essential for cellular life. Proteins with specific structural features including constricting rings, helical scaffolds, and hydrophobic membrane insertions are thought to be the primary drivers of fission. In contrast, here we report a mechanism of fission that is independent of protein structure-steric pressure among membrane-bound proteins. In particular, random collisions among crowded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
161
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 84 publications
11
161
1
Order By: Relevance
“…In contrast, recent work from our group found that protein crowding can drive membrane fission independent of protein structural or assembly properties (Snead et al, 2017). Specifically, molecular crowding among proteins attached to membrane surfaces at high density generates steric pressure that can bend membranes and ultimately overcome the energetic barrier to membrane fission (Busch et al, 2015; Snead et al, 2017; Stachowiak et al, 2012).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In contrast, recent work from our group found that protein crowding can drive membrane fission independent of protein structural or assembly properties (Snead et al, 2017). Specifically, molecular crowding among proteins attached to membrane surfaces at high density generates steric pressure that can bend membranes and ultimately overcome the energetic barrier to membrane fission (Busch et al, 2015; Snead et al, 2017; Stachowiak et al, 2012).…”
Section: Introductionmentioning
confidence: 78%
“…In contrast, recent work from our group found that protein crowding can drive membrane fission independent of protein structural or assembly properties (Snead et al, 2017). Specifically, molecular crowding among proteins attached to membrane surfaces at high density generates steric pressure that can bend membranes and ultimately overcome the energetic barrier to membrane fission (Busch et al, 2015; Snead et al, 2017; Stachowiak et al, 2012). In support of this mechanism, we found that bulky, intrinsically disordered proteins, which occupy significantly larger membrane footprints in comparison to well-folded proteins of similar mass (Hofmann et al, 2012), can be potent drivers of membrane fission.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…13 A recent report suggests lateral pressure from protein crowding can stretch and bend the membrane and lead to membrane fission. 14 Additionally, theoretical analysis has shown that crowded membrane-bound proteins generate substantial pressure at membrane surfaces. 15 These observations suggest crowding of proteins locally confined on the membrane surface, such as a region of membrane phase separation, may function as a general mechanism of membrane bending regardless of the specific protein structures involved.…”
Section: Introductionmentioning
confidence: 99%